An analysis of clinical predictive values for radiographic pneumonia in children. Issue 8 (13th August 2020) - Rees, Chris A; Basnet, Sudha; Gentile, Angela; Gessner, Bradford D; Kartasasmita, Cissy B; Lucero, Marilla; Martinez, Luis; O'Grady, Kerry-Ann F; Ruvinsky, Raul O; Turner, Claudia; Campbell, Harry; Nair, Harish; et al.
Abstract : Introduction: Healthcare providers in resource-limited settings rely on the presence of tachypnoea and chest indrawing to establish a diagnosis of pneumonia in children. We aimed to determine the test characteristics of commonly assessed signs and symptoms for the radiographic diagnosis of pneumonia in children 0–59 months of age. Methods: We conducted an analysis using patient-level pooled data from 41 shared datasets of paediatric pneumonia. We included hospital-based studies in which >80% of children had chest radiography performed. Primary endpoint pneumonia (presence of dense opacity occupying a portion or entire lobe of the lung or presence of pleural effusion on chest radiograph) was used as the reference criterion radiographic standard. We assessed the sensitivity, specificity, and likelihood ratios for clinical findings, and combinations of findings, for the diagnosis of primary endpoint pneumonia among children 0–59 months of age. Results: Ten studies met inclusion criteria comprising 15 029 children; 24.9% (n=3743) had radiographic pneumonia. The presence of age-based tachypnoea demonstrated a sensitivity of 0.92 and a specificity of 0.22 while lower chest indrawing revealed a sensitivity of 0.74 and specificity of 0.15 for the diagnosis of radiographic pneumonia. The sensitivity and specificity for oxygen saturation <90% was 0.40 and 0.67, respectively, and was 0.17 and 0.88 for oxygen saturation <85%. Specificity was improved when individual clinical factors such as tachypnoea, fever and hypoxaemia were combined, however, the sensitivity was lower. Conclusions: No single sign or symptom was strongly associated with radiographic primary end point pneumonia in children. Performance characteristics were improved by combining individual signs and symptoms.